A Companion to Byzantine Italy
1 online resource.
Keywords: This book offers a collection of essays on Byzantine Italy, the area from which we have inherited the richest and best-preserved historical evidence among all of the regions of the former Eastern Roman Empire up to the 11th century. The collection aims to provide readers with a critical overview of current research as well as new insights concerning political, institutional, economic, social, cultural and environmental aspects of the Italian regions under Byzantine rule. The methodological approach of the volume combines history with archaeology and art history, while remaining focused on the general framework of the early medieval Mediterranean. The result is a fresh and up-to-date synthesis that can be useful both for specialists and students.